Analysis of Constructivism Learning Model in Improving Cognitive in Elementary School Age Children - Rezani Ahzim (CV Media Inti Teknologi, 2023)
The learning process certainly has its own way of achieving a learning goal. As is the case with the learning model applied at SDN 32 to achieve learning objectives. The formulation of the problem raised by the researcher is, 1) how is the constructivism learning process at SDN 32 Rejang Lebong? 2) what are the teachers' views on constructivism learning? and 3) what are the obstacles in implementing constructivism learning. The purpose of the research is to find out the constructivism learning model in improving cognitive in elementary school children. The research design of this study is qualitative research that uses observation checklists, interviews, and notes as instruments to collect data. The population in this study was 200 people consisting of 20 teachers and 180 students of SDN 32 Rejang Lebong. The sampling technique was non-random sampling technique. The results found based on the results of observations and interviews are the implementation of constructivism learning is successfully applied to high grade elementary school children and has not been effectively applied to low grade children. In addition, teachers also gave positive responses to constructivism learning, namely with this learning, children become active and make more effort to gain knowledge. The obstacles found are the lack of facilities and infrastructure in the learning process.